PLEASE HURRY WILL GIVE POINTS AND BRAINLYEST TO FIRST RIGHT!!!
![PLEASE HURRY WILL GIVE POINTS AND BRAINLYEST TO FIRST RIGHT class=](https://us-static.z-dn.net/files/dc3/d7fc4421f9e3f383a7077df0e17a00e8.png)
Answer:
(0, 4) and (-1, 0)
Step-by-step explanation:
Given system of equations:
[tex]\begin{cases}y=2x^2+6x+4\\y=-4x^2+4\end{cases}[/tex]
Solve by substitution
Substitute the first equation into the second:
[tex]\implies 2x^2+6x+4=-4x^2+4[/tex]
Add 4x² to both sides:
[tex]\implies 2x^2+6x+4+4x^2=-4x^2+4+4x^2[/tex]
[tex]\implies 6x^2+6x+4=4[/tex]
Subtract 4 from both sides:
[tex]\implies 6x^2+6x+4-4=4-4[/tex]
[tex]\implies 6x^2+6x=0[/tex]
Factor out 6x from the left side:
[tex]\implies 6x(x+1)=0[/tex]
Therefore:
[tex]\implies 6x=0 \implies x=0[/tex]
[tex]\implies x+1=0 \implies x=-1[/tex]
To find the y-coordinates of the found x-values, substitute the found values of x into one of the equations:
[tex]x=0 \implies -4(0)^2+4=4 \implies (0,4)[/tex]
[tex]x=-1\implies -4(-1)^2+4=0\implies (-1,0)[/tex]
Therefore, the solutions to the system of equations are:
(0, 4) and (-1, 0)
Answer:
Solutions:
a) x = 0, y = 4 ⇒ (0, 4)
b) x = -1, y = 0 ⇒ (-1, 0)
Step-by-step explanation:
Given system of equations:
a) y = 2x² + 6x + 4
b) y = -4x² + 4
1. Substitute the value of y in the second equation into the first equation:
⇒ -4x² + 4 = 2x² + 6x + 4
2. Solve for x:
⇒ -4x² + 4 = 2x² + 6x + 4 [subtract 4 from both sides]
⇒ -4x² + 4 - 4 = 2x² + 6x + 4 - 4
⇒ -4x² = 2x² + 6x [subtract 2x² from both sides]
⇒ -4x² - 2x² = 2x² - 2x² + 6x
⇒ -6x² = 6x [subtract 6x from both sides]
⇒ -6x² - 6x = 6x - 6x
⇒ -6x² - 6x = 0 [factor out -6x from the equation]
⇒ -6x(x + 1) = 0
Two cases:
a)
⇒ -6x = 0 [divide both sides by -6]
⇒ -6x ÷ -6 = 0 ÷ -6
⇒ x = 0
b)
⇒ x + 1 = 0 [subtract 1 from both sides]
⇒ x + 1 - 1 = 0 - 1
⇒ x = -1
3. Find the value of y by substituting the found x values into one of the given equations:
a) x = 0:
⇒ y = -4x² + 4
⇒ y = -4(0)² + 4
⇒ y = -4(0) + 4
⇒ y = = 0 + 4
⇒ y = 4
coordinate: (0, 4)
b) x = -1:
⇒ y = -4x² + 4
⇒ y = -4(-1)² + 4
⇒ y = -4(1) + 4
⇒ y = -4 + 4
⇒ y = 0
coordinate: (-1, 0)
Learn more here:
brainly.com/question/27850666
brainly.com/question/27276129